Association between malnutrition and negative health outcomes in Italian older adults: findings from the ilSIRENTE study - Coelho-Júnior, Hélio José; Calvani, Riccardo; Russo, Andrea; Landi, Francesco; Marzetti, Emanuele (Frontiers in Nutrition, 2025)
IntroductionMalnutrition has been shown to contribute to adverse outcomes such as falls, fractures, and disability in older adults. However, findings remain conflicting, partly due to differences in operationalization methods. The recent adoption of the Global Leadership Initiative on Malnutrition (GLIM) criteria has shown promise, but evidence—especially in community-dwelling populations—is still limited and inconclusive. Therefore, the present study examined the associations between malnutrition and health-related parameters, including falls, fall-related fractures, disability, and mortality, in community-dwelling older adults.MethodsThis prospective cohort study involved octogenarians who lived in the mountain community of the Sirente geographic area in Central Italy. Malnutrition was defined according to the GLIM criteria. History of falls, incident falls, fall-related fractures, and disability status according to basic activities of daily living were recorded over 2 years. Survival status was obtained from participants’ general practitioners and verified through the National Death Registry, up to 10 years from enrollment. Binary, ordinal, and Cox regression analyses were performed to evaluate the associations between malnutrition and health outcomes.ResultsData from 334 older adults (mean age: 86.3 ± 4.7 years) were analyzed. Malnutrition was significantly and inversely associated with a history of falls, with non-malnourished individuals being less likely to have experienced a higher number of falls. However, no significant associations were found between malnutrition and the incidence of falls, fall-related fractures, disability (prevalence and incidence), or mortality.ConclusionThe findings of the present study indicate that malnutrition, as defined by the GLIM criteria, is significantly associated with a history of falls in older adults. Further studies examining important covariates are required to confirm our findings and expand the current knowledge in the field.